Open ateliers : inpakken & wegwezen. - Artoteek-Oost, Amsterdam; Dijkhuizen, Antje; Jansen, Steven (Amsterdam : Galerie Outline, 1998)
Andriese, Karin ; van den Anker, Mirjam ; Aschkenasy, Yair ; Beumer, Marian ; Bischof, Mark ; de Bont, John ; Brüggen, Thea ; van Buuren, Bas ; de Cleen, Claudie ; Degenhart, George ; Diemel, Jodokus ; Gerritsen, Peter ; Goulooze, Hinke ; Hardmeier, Barbara ; Houtkoop, Hannie ; Jager, Dirk Jan ; Jansen, Steven ; De Jong, Jeltje ; Ovetchkine, Andrei ; Paauw, Rick ; van Rees, Jan Theun ; van Rijn, Monica ; van Schalck, Antoinette ; van der Steit, Huib ; Veeninga, Mette ; Voorthuysen, Aernout ; van Vugt, Erik ; Weber, Anke ; van der Weg, Anita ; Xiao-Feng, Li ; Zamini, Behdokht
geboortejaar per kunstenaar
Inpakken en wegwezen, Galerie Outline, Amsterdam, 7 & 8 november 1998
Nederlands
kunstcatalogus